Stationarity of aftershock activities of the 2016 Central Tottori Prefecture earthquake revealed by dense seismic observation - Yoshihisa Iio (Earth, Planets and Space, 2020)
Abstract To clarify the relationship between earthquake occurrence and fluid, we analyzed data from a dense aftershock-observation network with 69 high-gain short-period seismographs installed immediately after the mainshock occurrence (October 21) in the aftershock area of the 2016 Central Tottori Prefecture earthquake. We determined the hypocenters and focal mechanisms of the aftershocks very precisely in the period from October 22 to December 15. We then investigated the temporal changes in the spatial distributions of hypocenters and T-axis azimuths of focal mechanisms. The distributions of aftershock hypocenters and T-axis azimuths are basically temporally stable, except those in limited portions in the shallow layer near the western edge of the aftershock area, where rapid decrease of aftershocks with T-axis azimuths of WSW to west was observed. If fluid rises from the lower crust due to fault rupture, the locations of aftershocks and focal mechanisms may change over time, especially in the deepest part of the aftershock region. However, the temporal change in these parameters was not apparent at depth. These observations suggest that the aftershock activity of the Central Tottori Prefecture earthquake was controlled mainly by stress concentration rather than strength reduction due to high fluid pressure.